Behavior and thermal comfort of light and dark coat dairy cows in the Eastern Amazon - Silva, Welligton Conceição da; Silva, Éder Bruno Rebelo da; Santos, Maria Roseane Pereira dos; Camargo Junior, Raimundo Nonato Colares; Barbosa, Antônio Vinicius Corrêa; Silva, Jamile Andréa Rodrigues da; Vinhote, Juliana Amaral; Sousa, Eudilene Dalet Vitor de; Lourenço Júnior, José de Brito (Frontiers in Veterinary Science, 2022)
This study aimed to evaluate the behavior and thermal comfort of 20 Girolando cows (5/8-H/G), with light and dark coats, in the wettest period of the year, in Santarém, Pará, Brazil, in pasture with access to shade, and plenty of drinking water and mineral salt. Animal behavior categories were computed for twelve hours a day, on three days in a row, by trained observers. Three day shifts were considered: Morning (6:00a.m. to 9:55a.m.), Intermediate (10:00a.m. to 01:55p.m.) and Afternoon (2:00p.m. to 05:55p.m.). The Temperature Index (TI), the Black Globe Humidity Index (BGHI) and the Comfort Index (CI) were calculated to measure thermal comfort. At all times studied, BGHI pointed that the environment was outside the thermal comfort zone. Dark-coated animals spent more 34.26% of the time in activities in the shade. The light-coated animals remained more 11.88% of the time in the sun, performing their natural behaviors. Both light and dark coat animals remained more 77% and 74.44% of the time in the sun, respectively. The behavior “in the sun while grazing” was the most evident, in both coats, in the studied shifts. The behaviors “in the shade while walking” and “in the shade while standing idle” were more evident (p<0.01) in dark-coated cattle. The grazing behavior was higher (p<0.05) in animals with dark coat (p<0.05). In all evaluated shifts, there was a positive correlation between the behavior “in the sun while grazing” with the CI (r= 0.44211; p<0.0305). Behaviors performed in the shade, such as “idleness while lying down”, “ruminating while lying down and standing up”, and behaviors “in the sun”, “idleness while lying down” and “ruminating while lying down”, were negatively correlated with CI. It is concluded that, even in the wettest period of the year, in the Eastern Amazon, Girolando dairy cows are exposed to hot environments, which causes thermal discomfort and changes in their natural behavior, as they spend more time standing in shaded areas, usually in rumination. Also, light-coated cows spend more time in the sun, while dark-coated cows spend more time in the shade.